The merits of the regional seas: programme for Southern Africa - Jepkosgei Boss, G (Institute of Marine and Environmental Law, 2023)
Regional Programmes for the Protection of the Marine Environment began with agencies and organisations that were mainly scientific in nature. These early organisations were research - oriented and although they could recommend action they had no regulatory powers, nor could they initiate any action. The oldest of such organisation is the International Council for the Exploration of the Sea (ICES) established in 1902. It was active in the North Atlantic and Baltic Sea areas carrying out scientific studies with investigations concerning exploitation of living and non-living marine resources. ICES later became involved with marine pollution studies and as a result set up a committee in 1960 to deal with it. In 1967 ICES set up a working group. This was one of the first signs of regional co-operation regarding the environment. Another such organisation was the Inter-Governmental Maritime Consultative Organisation (IMCO) now International Maritime Organisation (IMO).